Chaperone–usher pathways: diversity and pilus assembly mechanism - Busch, Andreas (The Royal Society, 2012)
Up to eight different types of secretion systems, and several more subtypes, have been described in Gram-negative bacteria. Here, we focus on the diversity and assembly mechanism of one of the best-studied secretion systems, the widespread chaperone–usher pathway known to assemble and secrete adhesive surface structures, called pili or fimbriae, which play essential roles in targeting bacterial pathogens to the host.